2003
DOI: 10.1016/s0304-3959(03)00333-6
|View full text |Cite
|
Sign up to set email alerts
|

Sweet taste and blood pressure-related analgesia

Abstract: To test the prediction that sweet taste modifies responses to cold induced pain, 72 young adults held sweet, bitter and water solutions in their mouths, in counterbalanced order, before and during a cold pain stimulus. To test whether or not blood pressure interacts with sweet taste analgesia, measurements of resting blood pressure were also obtained. A significant main effect of taste on pain tolerance was observed, as well as a significant interaction between resting mean arterial pressure (MAP) and taste on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 27 publications
3
41
2
Order By: Relevance
“…Laboratory experiments have also demonstrated that sweet-tasting substances may provide analgesic effects during acute stressors, e.g. increasing pain threshold latency and pain tolerance during cold-pressor tasks [42,43]. Taken together, these findings suggest a general capability of comfort foods to elicit desirable affective or sensory responses in humans, which may function to reinforce stress-induced eating behavior.…”
Section: Reinforcement Of Stress-induced Eating Via Affective Responsmentioning
confidence: 87%
“…Laboratory experiments have also demonstrated that sweet-tasting substances may provide analgesic effects during acute stressors, e.g. increasing pain threshold latency and pain tolerance during cold-pressor tasks [42,43]. Taken together, these findings suggest a general capability of comfort foods to elicit desirable affective or sensory responses in humans, which may function to reinforce stress-induced eating behavior.…”
Section: Reinforcement Of Stress-induced Eating Via Affective Responsmentioning
confidence: 87%
“…Nevertheless, more research is warranted before one can conclude that sucrose is an ineffective analgesic during adulthood. For example, the efficacy of sweet taste in reducing pain appears to be moderated by resting blood pressure in normotensive young adults (Lewkowski, et al, 2003). That the increased pain tolerance induced by sweet tastes during the CPT was attenuated in individuals with high-normal blood pressure suggests that they may not be as sensitive to opioid-mediated sweet-taste analgesia, perhaps because of opioid dysregulation (Lewkowski et al, 2003;see Bruehl and Chung, 2004 for review).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the efficacy of sweet taste in reducing pain appears to be moderated by resting blood pressure in normotensive young adults (Lewkowski, et al, 2003). That the increased pain tolerance induced by sweet tastes during the CPT was attenuated in individuals with high-normal blood pressure suggests that they may not be as sensitive to opioid-mediated sweet-taste analgesia, perhaps because of opioid dysregulation (Lewkowski et al, 2003;see Bruehl and Chung, 2004 for review). Whether the large proportion of overweight/obese individuals in the adult sample contributed to the lack of the analgesic effect is an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food 'liking' is conveyed to the frontotemporal cortical structures (Berridge, 2003;Kelley, 2004b) through m-opioid neurotransmission within the scattered network of subcortical and brainstem nuclei (Tanda and Di Chiara, 1998;Saper et al, 2002;Berridge, 2003;Berridge and Robinson, 2003;Pecina et al, 2003;Berthoud, 2004b;Kelley, 2004b;, including the NAc, VTA, ventral pallidum, nucleus of the solitary tract, parabrachial nucleus, and the amygdala. Opioids enhance food pleasantness (Doyle et al, 1993;Pecina and Berridge, 1995;, whereas consumption of high-energy sweet and fat food increases endogenous opiates release (ie, feedforward interaction; Tanda and Di Chiara, 1998;Colantuoni et al, 2002;Grigson, 2002) so that analgesia (Mercer and Holder, 1997a;Segato et al, 1997;Lewkowski et al, 2003), opioid dependence (Schoenbaum et al, 1989(Schoenbaum et al, , 1990Colantuoni et al, 2001Colantuoni et al, , 2002, and compensatory decrease of opiate gene expression in the reward structures (Kelley et al, , 2005 may ensue.…”
Section: Neurobiology Of Systems Mediating Food Rewardmentioning
confidence: 99%